2013
DOI: 10.5254/rct.13.87992
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Oil Plasticizers as Replacement of Petroleum Oil in Rubber

Abstract: Polymerized soybean oils of different molecular weights were used as plasticizers in NR/SBR compositions. The oils of different molecular weights and viscosities were synthesized by cationic polymerization using a proprietary technology. Because vegetable oils have double bonds, they are not only viscosity depressants but also active participants in cross-linking reactions. Properties of elastomers extended with different concentrations of mineral oil or pure soybean oil were compared with elastomers extended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
83
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 8 publications
6
83
0
Order By: Relevance
“…This effect is due to the introduction of norbornyl groups to the SO. Similar effect was also observed in the sulfur‐cured EPDM and SBR vulcanizates. After decreasing the oil level to 10 phr, various IIR vulcanizates exhibit a slightly increased T g , but still in the same order with respect of various oils.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…This effect is due to the introduction of norbornyl groups to the SO. Similar effect was also observed in the sulfur‐cured EPDM and SBR vulcanizates. After decreasing the oil level to 10 phr, various IIR vulcanizates exhibit a slightly increased T g , but still in the same order with respect of various oils.…”
Section: Resultssupporting
confidence: 76%
“…It is an excellent alternative oil resource for the rubber industry. Previous studies investigated the replacement of petroleum‐based plasticizers by SO in styrene‐butadiene rubber (SBR), natural rubber (NR), polychloroprene rubber (CR), ethylene‐propylene‐diene rubber (EPDM), and rubber blends . It was found that SO could be a replacement of petroleum‐based rubber plasticizers in various rubber compounds, but with some deficiency in certain properties.…”
Section: Introductionmentioning
confidence: 99%
“…It is already confirmed that TSO is an excellent plasticizer for EPDM from our previous work 10 ; however, it was also found that the introduction of TSO reduced the crosslinking density because the double bonds of TSO could react with the crosslinker. Petrović synthesized polymerized soybean oil by cationic method and successfully reduced the influence of soybean oil on crosslinking density . In this study, three HTSOs with different degrees of hydrogenation were prepared by hydrogenation of TSO to reduce the amounts of double bonds.…”
Section: Resultsmentioning
confidence: 99%
“…In Ref. [8] it is reported that soybean oil could be substituted for conventional oil in natural and styrene butadiene rubbers with minimal differences in mechanical and dynamic properties. The effects of replacing a portion of petroleum oil with soy-based oils on the cure kinetics and mechanical properties of EPDM (ethylene propylene diene monomer) rubbers have been investigated in Ref.…”
Section: Introductionmentioning
confidence: 99%